A 3D haloplumbate framework constructed from unprecedented Lindqvist-like highly coordinated [Pb6Br25]13- nanoclusters with temperature-dependent emission - Li, Xinxiong (2020)
Searching novel haloplumbate building units to construct three-dimensional (3D) frameworks is very important and highly desirable because such materials would possess new physical properties and potential applications. Here, by employing tetrakis(N-imidazolemethylene)methane(TIMM) as a structure-directing agent, the first 3D haloplumbate framework constructed from unprecedented Lindqvist-like highly coordinated [Pb6 Br25 ]13- nanoclusters has been successfully prepared under hydrothermal condition, where all Pb2+ centres in [Pb6 Br25 ]13- nanoclusters adopt seven-/eight-coordinated configurations. The as-obtained material is a wide-gap semiconductor (≈3.1 eV) and can be stable up to 320 °C. More importantly, this material has been demonstrated to show temperature-dependent emission. Our results could provide a new strategy to explore novel metal-halide open-framework materials.